Pengembangan Soal Serupa Trends In International Science Study (TIMSS) untuk Mengukur Kemampuan Berpikir Kritis dalam Pemecahan Masalah pada Siswa Kelas IV SD - Kuncoro, Debbi Dwi Wahyu; , Prof.Dr.Budi Murtiyasa, M.Kom (2016)
This research was intended to produce about timss to fourth grade are valid and practical. Methods used in this research is a method of research and development. This research need the two stages, namely preliminary and formative evaluation which includes self evaluation , experts review , one-to-one , small group , and field test. Technique data collection there were four that is used, interview, observation, documentation, and tringulasi. Technique data analysis there are three step , namely ( 1 ) preparatory , ( 2 ) tabulation , ( 3 ) the application of the data in accordance with the approach research. After going through stage one-to-one , small group , and validation a sort of descriptive set , about tried out at the field test in the class v-b primary school muhammadiyah special programs kottabarat. The results of the test at the one-to-one student average score is 87.50 , at the small group student average score is 85.56 , and at the field test student average score is 71.30 , so that it can be said , development about timss this have an effect potential for measuring the capacity to think critical in problem solving students.